Dampak Finansial Teknologi terhadap Hukum Perikatan di Indonesia - Fatur Faturohman; Sindi Susanti; Zfika Amanda Fitria Azil Rahmawati Fauziah (Letterlijk, 2024)
This article discusses the impact of online agreements on the law of engagement. Increasingly complex growth and development in society must be accompanied and followed by developments and regulations that can fill or provide protection for the legal needs required by society. However, with the ease of carrying out financing transactions through financial technology, parties who enter into agreements online are vulnerable and have a high potential for bad faith from other parties in entering into an agreement. The research method used is a normative legal research method with a deeper understanding of secondary information in the form of literature reviews and statutory regulations, and related literature. The results of the research show that legal protection for the parties involved is regulated in POJK NO.77/2016, the rapid development of the digital world and progress every year cannot be avoided by online-based technology, this innovation greatly influences the lifestyle of the economic community and of course provides development also to the law of Engagement.